SiC- and Ag-SiC-Doped Hydroxyapatite Coatings Grown Using Magnetron Sputtering on Ti Alloy for Biomedical Application; Coatings; Vol. 12, iss. 2 - Pana I. Iulian; Braic V. T. Viorel; Vladesku A. Alina; Ion R. Raluca; Parau A. C. Anca Constantina; Zoita N. C. Nicolae Catalin; Dinu M. Mihaela; Kiss A. E. Adrian; Cimpean A. Anisoara; Braic M. Mariana (2022, 2022)
Title screen